THE MEDIATING EFFECT OF ABSORPTIVE CAPACITY ON THE RELATIONSHIP BETWEEN SOCIAL CAPITAL AND TECHNOLOGY TRANSFER PERFORMANCE (Journal of Technology and Operations Management, 2015)
Social capital and absorptive capacity were highlighted as crucial to ensure the realization of the success of technology transfer. The study presented in this article investigate the effect of social capital and absorptive capacity on technology transfers performance by focusing on the technology advantages as the output of the transfer activities. Hypotheses were developed and tested by using data gathered through a survey on high technology companies operating in Malaysia technology parks. Correlation and regression analysis were executed by using SPSS 19. Based on the results of the study, social capital appears to be a prerequisite for the realization of technology transfer as it is the unique interconnectivity of human capital which will provide some technology players with an advantage over those who are not so well-connected. It was found that both social capital and absorptive capacity have significant effect on the performance of technology transfer. The findings also indicated that the elements of absorptive capacity mediate the effects of social capital on technology advantages in terms of relational and cognitive dimension. This study possibly will contribute in enhancing the performance of technology transfer especially in terms of the firm’s human resource capability and management capability.